PERLINDUNGAN TERHADAP TRANSAKSI YANG MENGGUNAKAN CEK KOSONG - Agung Williyas; Jasman Nazar (JOURNAL OF LAW AND NATION, 2024)
This study aims to explore the issue of transactions involving blank checks. The author's research strategy combines a legislative approach with a literature review to conduct normative legal analysis. The findings of this study illustrate the impact and available legal options arising from blank check transactions. Because it is considered easy to use and gives the issuer a sense of confidence, checks are becoming increasingly common. A check is one of the securities covered by the Commercial Code. But there are many abuses of the cheque issuance process when a blank cheque is issued. The importance of using checks to enforce rights in transactions based on relevant regulations is implied in this study